Efeitos da adição de mananoproteínas derivadas da parede celular de leveduras sobre parâmetros imunológicos de cães adultos e idosos - Kroll, Fernanda Sant Anna [UNESP] (2014)
It is believed that the active fractions mananoproteínas (AFM), obtained from the extraction and fractionation of cell wall of yeast (Saccharomyces cerevisiae), may beneficially modulate the immune system. This study evaluated the immunological effects of FAM in adults or elderly dogs. Three extruded diets with isonutritives including 0% (T0); 0.04% (T400) and 0.08% of AFM (T800) were used. In total, 36 beagle dogs were used. The treatments resulted from the combination of age (adults and elderly) and diet (T0, T400 and T800), generating six experimental treatments. For each diet six adult dogs (4.0 ± 2.0 years) and six elderly dogs (11.0 ± 1.0 years) were used. The experiment was randomized complete block design with three blocks of 12 dogs (six older and six adults, two dogs by age and diet). At zero, 14 and 28 days, blood samples were collected for phenotyping of blood leukocytes and evaluation of phagocytic activity. In zero and 28 days, hemogram, biochemical analysis, lymphocyte proliferation, production of hydrogen peroxide (H2O2), nitric oxide (NO), evaluation of the concentration of fecal immunoglobulin A and delayed test hypersensitivity (DTH) were performed. Data were subjected to analysis of variance with repeated measures, except DTH, in which we analyzed separately each time the trial period. Means were compared by Tukey test (p≤0.05). The AFM was safe in the levels and periods. At 28 days, adult dogs fed the diet T400 relative to T0 had higher counts of total lymphocytes (p<0.05). By analyzing the phenotype of the blood leucocytes was shown that, more specifically, adult dogs consuming 0.04% of the AFM increased the amount of total T-lymphocytes (p=0.05). Regardless of age, neutrophils from dogs fed T400, relative to T0 diet, tended to produce more H2O2 (p=0.09). Higher percentage of phagocytic activity of neutrophils were observed in adult dogs fed on T400 compared to the T800 diet (p<0.05). The skin response ...